SOCIAL MEDIA AND CONSUMER COMMUNICATIONS IN CRISIS PERIODS - Durukan, Tulin; Bozaci, Ibrahim (British Journal of Marketing Studies, 2014)
Social media is used for several consumption related communications like word of mouth, information search, and information sharing and communicating with firm. Also, social media is used for reaching information about social fluctuations like social, economic and political crises. Researches indicate that the level of being effected by a crisis is related with various changes in consumption behavior. At this point, the role of social media has not been researched in spreading crises related messages among people. So, present study asserts that consumption behavior of people may differentiate in terms of crises awareness, information level and negative perceptions about crises due to using social media for crisis communication. At last, suggestions for researches and companies are made